Dissolution Kinetics of Soil Kaolinite Derivative - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Acid dissolutions of soil kaolinite were carried out in two series of experiments. The first series involved dissolution of kaolinite in HCl with 3 levels (I N, 2N and 3N) of acid strength at 60 °C. The aim of this experiment was to study the effects of acid strength and temperature on the dissolution rate of kaolinite. The dissolution reactions were not carried to completion. The second series was conducted at a higher temperature (80° C) but with only 1 level (2 N HCI) of acid strength was applied and the dissolution reactions were carried to completion. The second series of the experiment was designed to evaluate the congruency of Fe, Al and Si released from kaolinite. Fe and Al released from kaolinite which are expressed as Fe, Al (d/t dissolved/total) during the first series of experiment increased st nngly with time. It was approximately linear initially (T. region) and became more curvy with progressive dissolution. Dissolution rate constant (a) also increased significantly as the acid strength increased from 1N, 2N and 3N HCI. The increasing value of a is about one-half and his about two folds as acid strength increased from IN to 2N and from 1N to 3N HCI respectively. The increase of temperature however, had a more astounding effect on the dissolution rate. The dissolution temperature change from 60 °C to 80 °C resulted in the dissolution rate being lifted 4.5 and 3 folds for Fe and Al respectively. The dissolution data within the limited initial linear region (TO of the first series of the experiment appeared to have fitted well to the cube root law. However, it inadequately described the dissolution data of the second series where the dissolution reactions were conducted to completion. For complete dissolution reactions, dissolution kinetics is best described with the modified first order of the Kabai's equation. Regression analysis shows that there is no significant relation between (a) and the properties of kaolinit analysed in this experiment. In contrast with the standard Georgia kaolinite, it has been found that for soil kaolinite the release of Fe, Al and Si occur at identical rate. Therefore, the dissolution is congruent which indicates that Fe, Al and Si in kaolinite under the present study are distributed uniformly within the crystal grains.